Life, law & liberty : a memoir - Kennedy, Anthony M., 1936- (Simon and Schuster, 2024)
"Anthony Kennedy's journey from an idyllic youth in 1940s Sacramento to service on the highest courts in America. Anthony Kennedy did not take the usual path to a seat on the Supreme Court. Often, the phrase "constitutional lawyer" brings to mind graduates of fine universities engaged in philosophic discourse as they walk the halls of government. Although Kennedy attended Stanford and the London School of Economics and then Harvard Law School, he made his way as a lawyer with a wide-ranging small-town practice that included criminal and civil trials, advice in forming and managing corporations, estate planning, and tax advice. For him, the law was not just an idea but a reality that touches Americans' lives every day. The nation's "little c" constitution-community, customs, and mores-proved as important as the "big C" Constitution adopted in 1789. Justice Antonin Scalia's one-time quip that the law is what "five Ivy-educated constitutional law professors say it is on a given day," may literally have captured Justice Kennedy-he was an Ivy-educated constitutional law professor. But the comment missed the distinctive background and mindset Justice brought to both the classroom and the bench. Born in Sacramento in 1936, the Irish-Catholic Kennedy grew up in a family active in civic affairs. The bookish youngster served as page in the California State Senate, but the teenager worked summers on oil rigs in Canada, Montana, and Louisiana. He attended Stanford and the London School of Economics, then went east to Harvard Law School. When he returned to Sacramento in 1963, it was to take over his late father's law practice. It was a busy and rewarding life, taking him into courtrooms and prisons. In addition, his work brought him into contact with the state's political elite. Kennedy and his wife helped the newly elected governor Ronald Reagan find a house in Sacramento in 1966, and he was in close consultation with those in Reagan's kitchen cabinet. Then in 1975, Gerald Ford appointed him to the federal judiciary. He was just thirty-eight and the youngest federal appellate court judge in the nation. His life now turned toward Washington, but it was Sacramento that was the making of a consequential jurist. When Kennedy left active service on the Supreme Court in 2018, Justice Neal Gorsuch noted, "As great as Justice Kennedy's legal legacy may be, I cannot help but wonder if today the person may have as much to teach us as the judge.""--